BEHAVIOURAL LOYALTY: APAKAH DIPENGARUHI BRAND PERSONALITY DAN BRAND EXPERIENCE? Sebuah Studi pada Industri Kosmetik - TRI WISMIARSI; TRULY JACKQUELINE PURNAMA (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
This study aimed to examine the effect of brand experience and brand personality on behavioral loyalty of beauty products. The data were collected from 200 respondents, women, who were above 20 years old and regular users of beauty products. Structured questionnaires were distributed to all respondents in a survey. The results show that brand experience and brand personality positively influence behavioral loyalty. The effect of brand personality on behavioral loyalty was greater than effect of brand experience on behavioral loyalty.